Synchrotron XANES and ED‐XRF analyses of fine‐paste ware from 13th to 14th century maritime Southeast Asia. (17th May 2017) - Jutimoosik, Jaru; Sirisathitkul, Chitnarong; Limmun, Wanida; Yimnirun, Rattikorn; Noonsuk, Wannasarn
Abstract : The combination of energy dispersive X‐ray fluorescence (ED‐XRF) and synchrotron X‐ray absorption near‐edge structure (XANES) provides the detailed composition of fine‐paste ware (FPW) kendis, dated back to 13th–14th century maritime Southeast Asia. Sources of clay and production sites were classified according to Al2 O3, SiO2, α‐Fe2 O3 and γ‐Fe2 O3 as well as trace elements. The similarities based on these components provided another evidence of a trade route between Kota Cina in North Sumatra of Indonesia and Kok Moh on Satingphra Peninsula, a well‐known production area in present‐day Thailand. In additions, the uniquely large contribution of α‐Fe2 O3 in XANES spectra suggests that Nakhon Si Thammarat province of Thailand could also be one of FPW production areas in maritime Southeast Asia. Copyright © 2017 John Wiley & Sons, Ltd.